CAMPUR KODE PADA ALBUM DON'T STOP OLEH AI CARINA UEMURA - Anni Asokawati; Irma Winingsih (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2015)
This study is aimed at analyzing the code mixing in Japanese songs using sociolinguistic approach. It describes the form of code mixing, the cause of code mixing in Japanese songs, and the influence of code mixing to the development of Weinreich language. The data analysed in this study are the sentences containing code mixing sung and composed by Ai Carina in Don’t Stop album. Those data were then analyzed using descriptive qualitative technique based on Suwito’s theory of code mixing, Bhatia and Ritchie’s code mixing influencing factors, and Weinreich and Mackey’s influence of code mixing. The resuts showed that the form of code mixing found in the songs are mostly outer code mixing in the form of clause. The factors influencing the code mixing are the desire to adapt the texts and the melody, as the emphasis of the story, as the tone appropriateness, to show the formal situation, to give the intrinsic message to the listeners, and to give emphasis to certain field. The influences of code mixing are dominantly in the form of interference in sentence level, they are word, phrase, and clause.Keywords : code mixing, interference, integration, influencing factors, sociolinguistics.